Enhancing AI Adoption in European SMEs: A Reference Model for Secure and Ethical Integration - Goebel, Marius (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
The rapid advancement of artificial intelligence (AI) offers significant benefits but also poses challenges, particularly for European Small and Medium Enterprises (SMEs). The aim of this dissertation project is to develop a reference model combining simplified Enterprise Architecture (EA) and Value-Sensitive Design (VSD) to facilitate secure and ethical AI adoption in European SMEs. AI systems can enhance efficiency and reduce costs but also introduce risks such as legal issues and reputational harm. SMEs, crucial to the European economy, face barriers like limited resources and regulatory concerns. Design Science Research (DSR) shall be employed to develop a reference model tailored to SMEs' needs, addressing technical, ethical, and social considerations. By addressing these challenges, the research aims to foster innovation and enhance SMEs' competitiveness, promoting broader AI adoption across the EU.